Toivonen, I., P. Csúri & E. van der Zee: Structures in the mind: Essay on language, music, and cognition in honor of Ray Jackendoff - Putnam, Michael T. (Norsk Lingvistisk Tidsskrift, 2017)
It is an insurmountable task to pay homage to the impact that Ray Jackendoff has had on the fields of cognitive science and linguistics more generally. The numerous publications and prestigious accolades alone (such as being the recipient of the Rumelhart Prize in Cognitive Science in 2014) signal his unique place in the field. Ida Toivonen, Piroska Csúri, and Emile van der Zee (TCV) have compiled an edited volume that contains essays from the various academic domains that Ray Jackendoff has contributed to over the course of his career. The introduction contains laudatory remarks from renowned scholars such as Paul Bloom, Noam Chomsky, Barbara Partee, and Steven Pinker, which together provide an impressive reflection on Jackendoff’s impact on these related disciplines.